An anaerobic-aerobic sequential batch system using simultaneous organic and nitrogen removal to treat intermittently discharged organic solid wastes. Issue 9 (September 2016) - Akizuki, Shinichi; Matsuyama, Tatsushi; Toda, Tatsuki
Graphical abstract: Highlights: Proposed combined organic and nitrogen removal in an anaerobic/aerobic batch system. Substrate COD was efficiently degraded by methanogenesis and denitrification. Higher recirculation ratios were favourable for enhancing the denitrification. Results showed that high recirculation during the active solubilization was optimal. Abstract: An anaerobic-aerobic sequential batch system using simultaneous organic and nitrogen removal was investigated to treat intermittently discharged organic solid wastes. Two different recirculation ratios of 10% and 20% day −1 of liquid volume of the anaerobic reactor were examined. In both conditions, methanogenesis occurred during the first 5 days of the process, whereas only denitrification occurred during the subsequent 10 days. At the end of the experiment, high COD removal efficiencies of 97.7% and 96.4% were achieved for the 10% and 20% day −1 recirculation ratios, respectively. A relatively large amount of COD consumed by denitrification was achieved for the 20% day −1 condition, indicating that an increase in the recirculation ratio enhances denitrification. Consequently, the final nitrogen removal efficiencies were 69.0% and 81.9% for the 10% and 20% day −1 recirculation ratios, respectively. To optimize the recirculation ratio, model equations were developed for the scale of this study. The modelling results demonstrated that high recirculation during the active solubilization period enhances the nitrogen removal efficiency. Recirculating 35% day −1 during the first 5 days and 10% day −1 during the subsequent 10 days is recommended as optimal for achieving high organic and nitrogen removal efficiencies.